The Challenge and The Prospect of Pesantren in Historical Review - Hamruni (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
In historical perspective, as an Islamic educational institution, pesantren has experienced a long journey. Until the present time, there are some pesantrens that still continue the heritage of old traditions. These pesantrens are named traditional pesantren. But some others, start to open themselves and make changes in responding to the present challenges.These kinds of pesantrens are called modern pesantren. The efforts of modernization by pesantren are dilematic enough because on one side, the modernization is needed, but on the other side, it contains a very different paradigm and world’s perspective. In such situation, pesantren have to discuss those differences with the Islamic paradigm and perpective as the heritage of Islamic civilization in the enlightment era. Hopefully, pesantren is able to figure out current problems smartly with contemporary approaches.